Digital Strategy for SMEs: Marketing Performance with e-Marketplace as a Mediation - Jayanti, Dewa Ayu Novi; Darma, Gede Sri (International Journal of Science and Society, 2024)
This research explores the impact of social media promotion, customer engagement, and marketing innovation on the marketing performance of MSMEs in Bali, with e-marketplace as a mediating variable. Using a sample of 200 MSMEs utilizing balimall.id, the SEM-PLS results indicate that social media promotion and marketing innovation significantly enhance marketing performance, while customer engagement does not have a direct impact. However, what distinguishes this study is the finding that the e-marketplace mediates the relationship between these three variables and marketing performance, strengthening the effects of promotion and innovation. The novelty of this research lies in the strategic role of the e-marketplace as a catalyst in the MSME digital ecosystem, where effective innovation and social media promotion can significantly improve marketing outcomes. This study is compelling as it provides new insights into how MSMEs can maximize the potential of digitalization through e-marketplace platforms to compete in a dynamic market.